Dissipation, residue, and distribution of pyraclostrobin in banana and soil under field conditions in South China. Issue 14 (13th November 2016) - Fu, Jiantao; Li, Zihao; Huang, Rilin; Wang, Shiying; Huang, Congling; Cheng, Dongmei; Zhang, Zhixiang
ABSTRACT: Two independent field trials were conducted in Guangdong and Guangxi, South China, in 2013, to study the dissipation, residue levels, and distribution of pyraclostrobin in banana and soil under field conditions. Pyraclostrobin residues were determined through a quick and effective method of high-performance liquid chromatography. Results showed that the average recoveries ranged from 80.55% to 98.08%, with relative standard deviations of 3.18–7.81% at three different spiking levels for each different matrix. The quantification limit of the proposed method was 0.006 mg/kg for both banana and soil. The half-lives of pyraclostrobin in bananas were 9.09 days in Guangdong and 8.26 days in Guangxi, and both bananas exhibited a dissipation rate of 90% after 28 days. The half-lives of pyraclostrobin in soil were 11.61 days in Guangdong and 10.60 days in Guangxi, with a dissipation rate of 90% after 35 days. Although several positive banana samples (i.e., pyraclostrobin exceeding the maximum residue limits (MRL) were found, the terminal residues in banana pulp were not detectable. All the terminal residues in banana pulp were below the MRL of 0.02 mg/kg, set by the Chinese Ministry of Agriculture, indicating a negligible risk associated with the exposure to pyraclostrobin via the consumption of banana. The distribution of pyraclostrobin in soil was also investigated in two experimental sites. The pyraclostrobin in different layer soil was time dependent and did not vary between the two sites. The result also showed that pyraclostrobin could be easily transported from the top soil to the subsoil. However, the highest quantity ratio did not exceed 10% in the bottom layer (20–30 cm). The distribution assessment also revealed that no significant potential environment risk was induced by pyraclostrobin in bananas.